The effect of sintering temperature on the microstructure and functional properties of BCZT-xCeO2 lead free ceramics. (June 2019) - Bijalwan, Vijay; Hughes, Hana; Pooladvand, Hojat; Tofel, Pavel; Nan, Bo; Holcman, Vladimir; Bai, Yang; Button, Tim W.
Graphical abstract: Highlights: Reduced sintering temperature ∼ 200 °C (i.e. 1350 °C) by an addition of 0.07 wt.% of CeO2 . High piezoelectric constant > 500 pC/N. Increased Curie temperature ∼ 105 °C. Detailed structural and microstructural studies. Detailed study on functional properties over CeO2 addition (0–3 wt.%) at different sintering temperatures. Abstract: We report (Ba0.85 Ca0.15 )(Zr0.1 Ti0.9 )O3 + x wt.% CeO2 lead free piezoelectric ceramics fabricated by conventional solid-state reaction routes. The phase structure, microstructure and functional properties have been systematically investigated. The morphotropic phase boundary was investigated in the range of x = 0 - 0.1%. A comparative study of their functional properties as a function of sintering temperature is presented. The study shows the important role of sintering temperature and grain size on the functional properties of these ceramics. Enhanced properties are observed for x = 0.07% at a sintering temperature 200 °C lower than for pure BCZT, in which, d33 = 507 ± 20 pC/N, kp  = 51.8%, εr  = 4091 ± 100, tan δ = 0.02, Pr  = 16.32 μm/cm 2, EC  = 2.13 kV/cm and TC  = 104.6 °C indicating that these ceramics are promising lead-free substitutes for the widely used lead-based ceramics.